Consequences of the disorders socio-policies on the Central African education system of 1991 to the year 2001: situation of primary education teaching - (:unkn) unknown (My University, 2006)
This work deals about the impacts both on supply and demand of education emerging from socio-political instability and trouble, the Sub Saharan geographical context. The targeted goal is to present a comparative analysis which indicates that countries could attain objective in the development of education if the context for civil peace appear satisfied. Then, by a historical and socio-political step, the study in the evolution of the school since its creation in the Central Africa case shows that multiple factors impacted within time duration the development of education. Lastly, the analysis of the consequences of the disorders encountered in the since the beginning of the Nineties reveals a quasi-total deliquescence in primary education. With the scope to rebuilt education sector, this work proposes alternative solutions in the light of analyses and experiments undertaken in similar countries which have to record similar events. However, the proposals for the agenda in developing advanced educational strategies which claim neither with completeness, nor with the unquestionable question of full effectiveness, should be evaluated under the scope for contributing to the formulation of an adequate educational policy in regards of Central Africa's singularity.
Keywords: African Research